Eco-Friendly Material Innovation in Sustainable Architectural Design - Adhita Nugraha Mestika; Suranto, Suranto (SEAN Institute, 2025)
The increasing urgency of environmental challenges has positioned sustainable architecture as a critical field within contemporary design practice. This article examines the latest innovations in environmentally friendly materials and their transformative impact on sustainable architectural design. Through a comprehensive qualitative analysis of recent developments, this research explores how bio-based materials, carbon-negative products, and circular economy principles are reshaping construction methodologies. The study reveals that emerging materials such as cross-laminated timber, mycelium-based composites, hempcrete, and carbon-capturing concrete offer significant environmental benefits while maintaining structural integrity and aesthetic appeal. These innovations demonstrate potential reductions in embodied carbon of up to 40% compared to conventional materials, while enabling buildings to achieve net-zero or carbon-negative status. The research also identifies key implementation challenges including cost considerations, regulatory frameworks, and the need for enhanced industry adoption. The findings suggest that the integration of these innovative materials, supported by advanced assessment methodologies and policy frameworks, represents a paradigmatic shift toward regenerative architectural practices that actively contribute to environmental restoration rather than merely minimizing harm